Comparison between rotational and glide techniques in shot put based on the performance analysis of competitions - Kato, T.; Maeda, K.; Mizushima, J. (Journal of Physical Education and Sport, 2023)
In shot put, both the glide and rotational techniques are used; however, the superiority of one technique over the other remains unclear. This study aimed to determine relative strengths and weaknesses of the glide and rotational techniques in shot put based on the analysis of competitive performance. Competition results for 176 male shot putters from international-level competitions held between 2001 and 2022 were collected. Their record, season`s best record (SB), the ratio of the record in the competition to season`s best record (%SB), and the rate of foul attempts were compared between the two techniques. The results showed that the mean %SB was higher for the glide technique compared to the rotational technique (glide: 97.31 ± 2.24%, rotational: 96.42 ± 2.28%, d = 0.39, p = 0.024). This indicates that the glide technique is better in maintaining a constant throwing action between each round. However, there was no difference in the %SB of the best record between the two techniques (rotational: 97.78 ± 2.58%, glide: 98.42 ± 2.55%, d = 0.25, p = 0.149). Additionally, the frequency of use of the throwing techniques (rotational: n = 130, glide: n = 46), the best record (rotational: 20.96 ± 0.87 m, glide: 20.67 ± 0.70 m, d = 0.35, p = 0.046) and SB (rotational: 21.44 ± 0.69 m, glide: 21.00 ± 0.48 m, d = 0.43, p< 0.001) were significantly higher for the rotational technique, and there was no significant difference in the rate of foul attempts. These findings show that the rotational technique is superior at achieving a higher performance, especially for recent international-level male shot putters.